1999
DOI: 10.1007/bf03044692
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic glycation and oxidative stress in chronic disease and diabetes mellitus

Abstract: Knowledge of the basis molecular mechanisms allows to understand the interplay of different inducers such as redicals, cytokines, AGE-proteins and amyloid-beta-peptids and to define oxidative stress as a "common endpoint" of cell dysfunction. With respect to therapeutic options it is now possible not only to optimize blood glycemic control, but also to design drugs such as AGE-inhibitors and AGE-"cross-link" breakers. In addition patients with chronic disease associated with increased oxidative stress ay benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 139 publications
0
10
0
3
Order By: Relevance
“…RAGE is a primary cell surface receptor for the S100/calgranulin ligand superfamily and EN-RAGE (extracellular newly identified RAGE-binding protein) (Nawroth et al, 1999). Cellular RAGE can bind with EN-RAGE in the endothelium on mononuclear phagocytes or lymphocytes to trigger cellular activation with the generation of key proinflammatory mediators such as TNF-a and CRP .…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is a primary cell surface receptor for the S100/calgranulin ligand superfamily and EN-RAGE (extracellular newly identified RAGE-binding protein) (Nawroth et al, 1999). Cellular RAGE can bind with EN-RAGE in the endothelium on mononuclear phagocytes or lymphocytes to trigger cellular activation with the generation of key proinflammatory mediators such as TNF-a and CRP .…”
Section: Discussionmentioning
confidence: 99%
“…Although both genetic and environmental factors appear to play a role, the cause of diabetes mellitus is still not clear. A large number of studies have demonstrated that oxidative stress and nonenzymatic protein glycation are closely associated with the development of diabetes mellitus (Nawroth et al, 1999;Vlassara and Palace, 2002). Antioxidants protect against glycationderived free radicals and may have therapeutic potential (Ceriello et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies on non‐enzymatic glycosylation have been carried out with higher eukaryotes, particularly humans, because of the clinical importance of this process and its relation to ageing (Chellan and Nagaraj, 1999; Nawroth et al ., 1999). There are only a few reports on non‐enzymatic glycosylation in lower eukaryotes.…”
Section: Introductionmentioning
confidence: 99%